The impact of parenting stress on parents of school-age children with drug-resistant epilepsy - Lu, Hsin-Hui; Tsai, Chun-Yu; Chou, I-Ching; Tsai, Jeng-Dau (Frontiers in Pediatrics, 2022)
Background: Psychological burdens can affect the quality of life among parents of children with epilepsy, especially parents of children with poor seizure control. The impact of stress on the parents of children with epilepsy is significantly comorbid with their children’s cognitive dysfunction and the severity of epilepsy. The aim of this study was to assess the stress levels of parents of school-age children with drug-resistant epilepsy (DRE) and controlled-epilepsy after considering the children’s cognitive ability. Methods: The study participants consisted of 35 children with typical development in the control group, 25 in the controlled-epilepsy group, 26 in the DRE group, and their parents. We used the parenting stress index (PSI) to measure the stress levels of all parents and the Wechsler intelligence scale for children (WISC) to assess the children’s cognition levels. Results: Parenting stress was significantly higher among the parents of children with DRE than of those in the control and controlled-epilepsy group. The PSI’s child domain showed statistically significant subscales of adaptability, acceptability, demandingness, and distractibility/hyperactivity. Moreover, the high-risk ratio on the acceptability subscale was higher for the DRE group than for the controlled-epilepsy group and for the control group. Conclusion: Seizure severity significantly influences parenting stress after considering cognitive dysfunction in children with epilepsy. Therefore, pediatricians and clinicians should consider epilepsy-specific stress in parents of children with DRE.